Social profit canvas : starting point for social profit and value - Vermeulen, M. (Marc), 1958-; Vroomen, Anke (Sun Media, 2022)
"Organizations in the public domain must be of value for the citizen, being a tenant, client, patient, student, etc. Foundations, corporations, associations, they all have the intention to make social profit and avoid financial loss. What is the real value and how do these organizations contribute? Social profit and value, that is where this book is about. We present a new method to visualize and assess this profit. The Social Profit Canvas aims to empower two things: increase result and impact, and effect a change towards a "bottom-up-approach". This book will lead and support professionals in the sector to achieve these goals. Marc Vermeulen and Anke Vroomen describe the developments in the public domain and explore the use of the Social Profit Canvas model, including measuring and decision making in respect of public value. The Social Profit Canvas is developed together with Mark Wolbert and Jaap Hoenderdos from WHISE (company for social profit creation) based on their practical experience combined with the scientific knowledge of TIAS (School for Business and Society)."--Publisher's description.
Keywords: Nonprofit organizations.; Nonprofit organizations -- Finance.; Community foundations.; Organizations, Nonprofit; Societies; Associations sans but lucratif.; Associations sans but lucratif -- Finances.; Fondations communautaires.; Associations.; nonprofit organizations.; Community foundations; Nonprofit organizations; Nonprofit organizations -- Finance